(untitled) (The Pakistan Development Review, 1998)
A major challenge to economic policy in Pakistan at this time is to energise the private SME sector of the economy. This follows in part from the fact that other sectors are unlikely, under present circumstances, to provide the needed growth either of output or of reasonably remunerative employment; in fact, there will be a major employment challenge over the coming years as labour supply continues to expand rapidly and as neither the large-scale private sector nor the public sector are poised to create significant numbers of jobs, and though agriculture and the non-agricultural microenterprise sector can and probably will do so the levels of productivity and hence of remuneration are likely to be unattractively low. By contrast, the SME sector does have substantial untapped potential to contribute to those objectives; both economic logic and the experiences of other developing countries point to that potential, as well as providing evidence on how it may be achieved. A dynamic SME sector is an important complement to a more open economy; in most of the countries which appear to have reaped major benefits from export orientation the SME sector has been importantly involved in that process. Achieving the maximum contribution from SME, however, will require significant improvements in the support system. If achieved it will not only constitute an important source of dynamism in and of itself, but will also complement efficient large enterprise, strengthen the demand for agricultural products, and make it easier for microenterprise to graduate into the SME size range.